Organizational and Regional Perceptions on Risk Status of Change Orders, Shop Drawing Practices and Claims and, Key Control Measures in Construction Projects - İlter, Osman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
One of the most common concerns in construction projects is changes in the construction execution process. Projects in the Turkish construction industry have exposure to many changes depending on many factors. Many variables affect construction projects during execution. There are various contract clause components that can contribute to changes in construction projects. In particular, shop drawing practices have an important effect on the change of contract drawings. On the other side, changes may allow contractors to claim additional price and duration. Any organizations involved in the project may have to meet the monetary value of the claim. The projects may be completed with failures because of claims and every part is in seeking to express their self-righteousness in such cases; conflict may arise between parties involved in projects. The reasons for the changes and claims may differ depending on the project parties, the project region, and the project characteristic. This research aims to examine the key events contributing to contract clauses named change orders, shop drawing practices, claims, and key control measures, based on a survey of construction professionals in the organizations and seeks to develop and propose the regional framework for Turkish construction industry which assists to construction organizations to control the problematic events encountered in construction projects. In this context, a variety of events leading to change were examined based on the perceptions of the organizations in Turkey, North Cyprus, Turkey, as well as in the U.S.A. On the other hand, a variety of events leading to shop drawing practices, and claims events and, in the final phase, a variety of potential measures that can be taken to prevent claims were examined based on the perceptions of the organizations in Turkey. The interaction status of key events of these contract clause components were examined in the perceptions of organizational characteristics. The events of change orders are also examined on the basis of developed and developing country characteristics. Descriptive method is used to analyse the survey data in numerical terms based on participants‘ replies. After that, analytical research approaches were adopted to explore the impact of organizational and regional characteristics concerning key events of these contract clauses. The research findings showed that the critical events of contract clauses and control measures differed by the characteristic and regional features. A total of 12 different (variable) most critical events are identified on the basis of variety of organizational perceptions. 3 of these events were for "change order", 5 of them were for "shop drawings" and 4 variable "contractors' claims" were determined. On the other hand, 5 variable control measures are identified with respect to organizational perceptions. According to the perceptions of the organizations, a framework model has been presented to indicate the critical triggering events of these contract clauses and effective control measures in construction projects for the Turkish construction sector.

ÖZ: İnşaat projelerindeki en yaygın kaygılardan biri de uygulama sırasındaki değişikliklerdir. İnşaat projelerine birçok değişkenlik, uygulama sürecinde etki etmektedir. Türk inşaat endistrisinde İnşaat Projeler birçok faktöre bağlı olarak değişikliklere maruz kalmaktadır. İnşaat projelerinde değişikliklere katkıda bulunabilecek çeşitli sözleşme maddesi bileşenleri vardır. Özellikle şantiyede çizim uygulamalarının sözleşme çizimlerinin değiştirilmesi üzerinde önemli bir etkiye sahiptir. Diğer taraftan, değişiklikler, yüklenicilerin ek fiyat ve süre talep etmesine olanak sağlamaktadır. Projede yer alan herhangi bir organizasyon, talebin parasal değerini karşılamak zorunda kalabilmektedir. Projeler talepler nedeniyle başarısızlıkla sonuçlanmakta ve bunun sonucunda taraflar arasında ciddi anlaşmazlılar doğmakta ve oluşan bu durum karşısında taraflar kendilerinin mağdur olduğunu ifade etme eğilimde olmakta ve oluşacak olan olumsuzluğun bedelini karşı tarafa ödetme eğilimde bulunmaktadırlar. Değişikliklerin ve taleplerin nedenleri proje taraflarına, proje bölgesine ve proje karaktersitiğine bağlı olarak değişebilmektedir. Bu tezin amacı, organizasyonel ve bölgesel karakteristiklerin, değiştirme talimatları, şantiye çizim uygulamaları, yüklenici talepleri, ve kilit kontrol önlemleri olarak adlandırılan sözleşme maddelerine katkıda bulunan en kritik olaylar üzerindeki etkisi irdelemek, ve Türk inşaat endüstrisindeki inşaat organizasyonları algısında, inşaat projelerinde karşılaşılan sorunlu olayların önlenebilmesi amacında, en kritik olaylara ve en etkili önlemlere dikkat çekmeye amaçlayan çerçeve modeli geliştirmeyi amaçlamaktadır. Bu bağlamda, İnşaat projelerinde değiştirme talimatlarına yol açabilen çeşitli olaylar Türkiye, Kuzey Kıbrıs ve de A.B.D. bulunan inşaat organizasyonlarının verilerine dayanarak incelenmiştir. Öte yandan, şantiye çizim uygulamalarına ve yüklenici taleplerine yol açabilen inşaat projelerinde karşılaşılabilen çeşitli olaylar, ve son süreçte de, taleplerin önlenebilmesi adına uygulanabilen çeşitli potansiyel önlem çeşitleri Türkiye'de yer alan inşaat organizasyonlarının algılarına dayanarak irdelenmiştir. Bu sözleşme maddesi bileşenlerinin anahtar olaylarının etkileşim durumu, organizasyonel özelliklerin algılarında incelenmiştir. Değiştirme talimatları olaylarını, gelişmiş ve gelişmekte olan ülke karakterisiği bazında irdeleme de yapılmıştır. Tanımlayıcı yöntem, Katıkımcıların yanıtlarına göre anket verilerini sayısal terimlerle analiz etmek için betimleme yöntemi kullanılmıştır. Daha sonra, analitik araştırma metodu yaklaşımları adapte edilerek bu sözleşme maddelerinin kilit olaylarıyla ilgili organizasyonel ve bölgesel özelliklerin etkisini irdelenmiştir. raştırma bulguları, sözleşme maddelerinin ve kontrol önlemlerinin kritik olaylarının organizasyonel ve bölgesel karakteristiğe göre farklılık gösterdiğini tespit edilmiştir. Çeşitli organizasyonel ve bölgesel algılar temelinde, toplam 12 farklı (değişken) kritik olay tespit edilmiştir. Bu kritik olayların 3'ü "değiştirme talimatları", 5'i "şantiye çizim uygulamaları" ve 4 değişken "yüklenici talepleri" adına belirlendi. Öte yandan organizasyonel algılara göre 5 değişken önleyici tedbir tanımlanmıştır. Organizasyonların algılarına göre, inşaat projelerinde bu sözleşme maddelerinin kritik tetikleyici olaylarını ve etkili kontrol önlemlerini belirtmek için Türk inşaat sektörü için çerçeve model sunulmuştur.
Doctor of Philosophy in Civil Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2021. Supervisor: Prof. Dr. Tahir Çelik.
Keywords: Civil Engineering Department; Project management--Construction Projects; Construction industry--Management--Project management--Time and Cost; Change orders, variation, cost-time overrun, claim, disputes, mitigation measures, shop drawing